Joyful Learning In Fiqh Lesson Using Vlog : A Case Study at 26 Muhammadiyah Kalitengah Islamic Junior High School Lamongan - Rusydiyah, Evi Fatimatur; Praja, Tatag Satria (State Islamic Institute of Madura, 2019)
The process of learning in the 21st century is oriented towards innovative and creative activity. One of it is the integration of ICT literacy in learning. Fiqh learning mostly taught conventionally so that it is uninteresting. Therefore, this research would like to focus on the joyful learning method. The phenomenon was that the teacher conducted the learning using ICT literacy and made the environment fun. The focus of this study is how the implementation of joyful learning in Fiqh lesson based on vlog was and how was the students’ response. The data was collected through observation, and interview. The result was 1) the implementation of vlog was started with introduction, core content, and conclusion. This made the environment fun; 2) students’ responses were taken from 6 indicators which were: fun, interesting, interactive, self-confidence, more interactive, new knowledge, and content understanding. 55% of the students answered, 49% of the students strongly agreed, 38% of the students agreed, and 13% of the students disagreed.